ANALISIS KARAKTER SISWA PADA MATA PELAJARAN IPA KELAS VIII SMPN 01 BANDAR MATARAM KABUPATEN LAMPUNG TENGAH TAHUN AJARAN 2024/2025 - Latifatus Sa’adah; Putri Ma’rifah; Desta Ayu Aprilia; Gita Sofica; Della Novita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze students' character development during the learning process of Integrated Natural and Social Sciences (IPAS) in Grade VIII at SMPN 01 Bandar Mataram, Central Lampung Regency, in the 2024/2025 academic year. The main focus of this research is on character values such as discipline, responsibility, honesty, cooperation, and curiosity demonstrated by students during classroom activities. The method used is descriptive qualitative, with data collected through observation, interviews with teachers and students, and documentation of learning activities. The results show that most students have shown positive character development, especially in terms of discipline and responsibility, such as arriving on time, completing assignments well, and working collaboratively in group discussions. However, some students still require further guidance, particularly in honesty and learning consistency. The conclusion of this study is that science learning can serve as an effective medium for character development if supported by appropriate teaching methods and the active role of teachers in guiding students' attitudes.